Study Regarding the Implementation of Traditional Law That Violates Women’s Human Rights in Indonesian National Law - Putri Deviana Insti; Winda Fitri (LEGAL BRIEF, 2022)
Indonesia is a country that has a higher population level, especially for women, where based on the Central Statistics Agency, as many as 137,521,557 people are men and 134,707,815 people are women or 49% of the total population in Indonesia. Equality and the elimination of discrimination against women are often the centers of attention and a shared commitment to implement them. However, in social life, the achievement of equality in the dignity of women has not shown significant progress. The issue of human rights and women has not been taken seriously by the state. The research method used is descriptive-analytical. This study indicates that the dominant factors of sexual violence against women are patriarchal culture, male privileges, and permissiveness. The main reason women victims of sexual violence do not report is the public’s bad stigma about victims of sexual violence. Assertive training can help women and victims of sexual violence to have the courage to refuse and express their feelings in the right way. The suggestion from this research is that there must be mutual respect and care between men and women